HUBUNGAN STRESS AKADEMIK DAN INDEKS MASSA TUBUH ( IMT ) DENGAN PREMENSTRUAL SYNDROME PADA SISWI KELAS 9 SMPN 1 SUMBERPUCUNG - Yunisari, Siti Zulaika; Panggayuh, Ardi; Kusmiwiyati, Ari (Poltekkes Kemenkes Malang, 2023)
Menstruation is bleeding that repeats every month and indicates that the female reproductive organs are ready to be fertilized. In the menstrual cycle, changes in hormone levels will occur when a young woman will experience menstruation. This can affect changes in the physical and emotional conditions of adolescent girls before menstruation, which is commonly referred to as premenstrual syndrome (Ministry of Women and Children Empowerment of the Republic of Indonesia, 2015). The prevalence of premenstrual syndrome in Indonesia is 70-90% in women of childbearing age and it is found that 2-10% are experiencing severe symptoms of premenstrual syndrome (Sari and Priyanto, 2018). The purpose of this study was to determine the relationship between academic stress and body mass index (BMI) with premenstrual syndrome in 9th grade students of SMPN 1 SUMBERPUCUNG. This type of research is a correlation design that uses a cross sectional approach. A sample of 31 9th grade students were selected using a total sampling technique. In research using Spearman Rank data analysis, there is a relationship between academic stress and premenstrual syndrome which results in value < (0.002 < 0.05). Meanwhile, the relationship between body mass index (BMI) and premenstrual syndrome produces a value of value < (0.015 < 0.05). based on the results of this study, students should be able to manage and control their emotions so that stress does not occur and always maintain a pattern eat to stay at a normal BMI.